Transition of young adults with endocrine and metabolic diseases: the 'TRANSEND' cohort. Issue 1 (January 2021) - Le Roux, Enora; Menesguen, Florence; Tejedor, Isabelle; Popelier, Marc; Halbron, Marine; Faucher, Pauline; Malivoir, Sabine; Pinto, Graziella; Léger, Juliane; Hatem, Stephane; Polak, Michel; Poitou, Christine; et al.
Abstract : Objective: The transition from paediatric to adult medicine involves risks of poor patient outcomes and of significant losses of patients to follow up. The research aimed to analyse the implementation in an initial cohort of patients of a new programme of transition to adult care based on a case management approach. Design: A longitudinal study of the case management approach to transition, initiated in a university hospital in France in September 2016. Methods: Patients with the endocrine or metabolic disease diagnosed during childhood and transferred to adult care were included. The transition programme includes three steps based on case management: liaising with paediatric services, personalising care pathways, and liaising with structures outside the hospital (general practitioners, agencies in the educational and social sector). Results: The cohort included 500 patients, with malignant brain tumour ( n  = 56 (11%)), obesity ( n  = 55 (11%)), type 1 diabetes ( n  = 54 (11%)), or other disease ( n  = 335 (67%)). Their median age at transfer was 19, and the sex ratio was 0.5. At median 21 months of follow-up, 439 (88%) had a regular follow-up in or outside the hospital, 47 (9%) had irregular follow-up (absence at the last appointment or no appointment scheduled within the time recommended), 4 had stopped care on doctor's advice, 4 had died, 3 had moved, and 3 had refused care. The programme involved 9615 case management actions; 7% of patients required more than 50 actions. Patients requiring most support were usually those affected by a rare genetic form of obesity. Conclusions: Case managers successfully addressed the complex needs of patients. Over time, the cohort will provide unprecedented long-term outcome results for patients with various conditions who experienced this form of transition.